Relationship between anthropometric and strength variables and maximal throwing velocity in female junior handball players - a pilot study - Javad Sarvestan; Václav Riedel; Zuzana Gonosová; Petr Linduška; Miroslava Přidalová (Palacký University Olomouc, 2019)
Background: Throwing velocity is one of the determinant scoring elements in handball. However, our knowledge of anthropometric factors and shoulder muscle strength among female players and how these affect throwing velocity is limited. Objective: This study aimed to assess the relationships between throwing velocity and the physical traits of anthropometric factors and shoulder muscle strength in female handball players. Methods: Nine elite female junior handball players (age 17.1 ± 1.7 years, body height 169.7 ± 3.8 cm, body mass 66.2 ± 6.8 kg, experience with handball 8.9 ± 1.7 years) participated in the study. Spearman's correlation coefficient was used to detect correlations between throwing velocity and shoulder internal rotator torque, explosive strength deficit, and anthropometric parameters of the upper limb. Results: Our results showed significant correlations between throwing velocity and upper limb length (r = .82) and hand length (r = .68); however, no significant correlations were observed between throwing velocity and shoulder internal rotator peak torque, explosive strength deficit, lean body mass of upper limb, and other anthropometric parameters. Conclusions: The results of this study suggest that the lengths of the upper limb and hand are the two main elements that affect throwing velocity in female handball players; this could be employed in talent identification.